COMMUNITY SERVICE: OPTIMIZING DIGITAL CAPACITY OF EMPLOYEES IN THE CULINARY SECTOR AT PANDEKA CAFE - Putri Meliza Sari; Stevani Stevani; Lovelly Dwinda Dahen; Yosi Eka Putri; Rika Verawati; Nisha Selvia; Meri Rayanti (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2026)
This community service program was conducted at Pandeka Cafe, Batusangkar, aiming to enhance the digital capacity of its employees in the culinary sector. The program focused on practical digital skills training, including the use of digital cash register systems, inventory management, and online marketing. A participatory approach was applied, involving workshops, guided practice, and collaborative problem-solving. Results demonstrated significant improvements in employees’ digital literacy, operational efficiency, and online promotion skills, contributing to increased productivity and enhanced service quality. This initiative provides a model for capacity-building interventions in small culinary businesses, showing that technology adoption can improve workforce competency and business performance.